COMPARISON OF EFFECTS OF MISOPROSTOL AND OMEPRAZOLE ON THE GASTROINTESTINAL COMPLICATIONS OF NONSTEROIDAL ANTI-INFLAMMATORY DRUGS - Tülay SARIÇAM; Nur ERSÖZ; Eser VARDARELİ and Ayşegül HARMANCI and Varol ŞAHİNTÜRK and Akif ALADAĞ and Esat ERENOĞLU (Turkish Journal of Gastroenterology, 2020)
-